Kluyveromyces lactis and Saccharomyces cerevisiae for Fermentation of Four Different Coffee Varieties - Danilo José Machado de Abreu; Denis Henrique Silva Nadaleti; Rafaela Pereira Andrade; Tamara Leite dos Santos; Dérica Gonçalves Tavares; Cesar Elias Botelho; Mário Lúcio Vilela de Resende; Whasley Ferreira Duarte (Foods)
One strategy for adding unique characteristics and flavors to improve coffee quality is the selection of starter microorganisms. Here, we aimed to evaluate the effect of Saccharomyces cerevisiae LNFCA11 and Kluyveromyces lactis B10 as starter cultures on the quality of four different wet-fermented coffee varieties. Microbiological, molecular, and chemical analyses were carried out to identify yeast, bacteria, volatile compounds, carbohydrates and bioactive compounds in coffee. Sensory analysis was performed by Q-graders certified in coffee. Starter yeasts affected bioactive and volatile compounds as well as sensory descriptors in the coffee varieties. S. cerevisiae CA11 allowed a higher content of trigonelline and chlorogenic acid in MGS Paraíso 2 (P2) and Catuai Amarelo IAC62 (CA62) varieties. K. lactis B10 fermentation resulted in higher chlorogenic acid only on the P2 cultivar and MGS Catucaí Pioneira (CP). In addition, 5-methyl-2-furfuryl alcohol and n-hexadecanoic acid were produced exclusively by yeast fermentation compared to spontaneous fermentation. The coffee cultivars P2 presented more complex sensory descriptors and the attributes of aroma, acidity, and balance when fermented with S. cerevisiae CA11. Sensory descriptors such as lemongrass, citrus, and lemon with honey were related to K. lactis B10. Starter cultures allowed the coffees to be classified as specialty coffees. The fermentation showed that the choice of starter yeast depends on the desired sensory descriptors in the final product.